The trade impact of European union preferential policies an analysis through gravity models - De Benedictis, Luca; Salvatici, Luca; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
The book investigates the EU preferential trade policy and, in particular, the impact it had on trade flows from developing countries. It shows that the capability of the "trade as aid" model to deliver its expected benefits to these countries crucially differs between preferential schemes and sectors. The book takes an eclectic but rigorous  approach to the econometric analysis by combining different specifications of the gravity model. An in-depth presentation of the gravity model is also included, providing significant insights into the distinctive features of this technique and its state-of-art implementation. The evidence produced in the book is extensively applied to the analysis of the EU preferential policies with substantial suggestions for future improvement. Additional electronic material can be found onli
Introduction -- EU Preferential Trading Arrangements: Evolution, Content and Use -- EU Preferential Margins: Measurement and Aggregation Issues -- The Gravity Model in International Trade -- Trade Impact of EU Preferential Policies: a Meta-analysis of the Literature -- Trade Impact of EU Preferences -- Analysing the Impact of Everything but Arms Initative Using a Gravity Model -- Trade Impact of EU Preferences: an Analysis with Monthly Data -- Trade Preference Through Tariff Rate Quotas and the Gravity Equation: Does the Tariff Equivalent Matter?- Trade Impact of EU Preferences: the Role of Compliance Costs
Electronic reproduction.
Keywords: Trade regulation -- European Union countries